Ozone Measurements Using the Refurbished Eureka Stratospheric Differential Absorption Lidar. Issue 3 (4th July 2019) - Tikhomirov, Alexey B.; Farhani, Ghazal; McCullough, Emily M.; Sica, Robert J.; Fogal, Pierre F.; Leblanc, Thierry; Drummond, James R.
Abstract: The Stratospheric Ozone Differential Absorption Lidar (DIAL) located at the Polar Environment Atmospheric Research Laboratory (PEARL) in Eureka, Nunavut (80°N, 86°W) has been a powerful tool for the measurement of stratospheric ozone vertical profiles in the Canadian High Arctic since 1993. The lidar ozone profiles measured during the 2017 Canadian Arctic Atmospheric Chemistry Experiment (ACE) and Optical Spectrograph and InfraRed Imaging System (OSIRIS) Validation Campaign were compared to coincident ozonesonde, ACE-FTS, ACE-MAESTRO and OSIRIS profiles. The results show the lidar overestimates the ozone by ∼10% in the 10 km–20 km altitude range on average in comparison with the ozonesonde. Above 20 km the profiles agree within 10%. The OSIRIS ozone agrees within 10% with DIAL ozone between 15 km and 41 km. A strong stratospheric ozone depletion event was seen on March 3, 2017, during which the ozone concentration dropped below 10 12 molecules cm –3 at the 15.5 km and below 6 × 10 12 molecules cm –3 at 16 km as measured by the ozonesonde and the lidar correspondingly. Laminated structures were observed in the ozonesonde profiles near the polar vortex edge regions. This together with non-optimal temporal and spatial coincidences between the measurements conducted by different instruments can affect validation accuracy.